2020
DOI: 10.1111/mmi.14638
|View full text |Cite
|
Sign up to set email alerts
|

Hemeprotein Tpx1 interacts with cell‐surface heme transporter Str3 in Schizosaccharomyces pombe

Abstract: Str3 is a transmembrane protein that mediates low-affinity heme uptake in Schizosaccharomyces pombe. Under iron-limiting conditions, Str3 remains at the cell surface in the presence of increasing hemin concentrations. Using a proximitydependent biotinylation approach coupled to mass spectrometry and coimmunoprecipitation assays, we report that the peroxiredoxin Tpx1 is a binding partner of Str3.Under microaerobic conditions, cells deficient in heme biosynthesis and lacking the heme receptor Shu1 exhibit poor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(37 citation statements)
references
References 58 publications
(118 reference statements)
0
37
0
Order By: Relevance
“…In our previous study (Normant et al, 2021), we reported the enrichment of S. pombe Tpx1 in the membrane fraction along with Str3 when cells are compelled to utilize the Str3-dependent hemin uptake system for growth. Under these conditions, some Tpx1 proteins form a heteroprotein complex with Str3, which is detectable through pull-down assays (Normant et al, 2021). Similarly, in this study, coimmunoprecipitation experiments showed the interaction between Srx1-Myc 12 and Str3-GFP proteins in iron-starved cells grown in the presence of hemin.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In our previous study (Normant et al, 2021), we reported the enrichment of S. pombe Tpx1 in the membrane fraction along with Str3 when cells are compelled to utilize the Str3-dependent hemin uptake system for growth. Under these conditions, some Tpx1 proteins form a heteroprotein complex with Str3, which is detectable through pull-down assays (Normant et al, 2021). Similarly, in this study, coimmunoprecipitation experiments showed the interaction between Srx1-Myc 12 and Str3-GFP proteins in iron-starved cells grown in the presence of hemin.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that Srx s interact with 2-Cys Prx s (Jönsson et al, 2008(Jönsson et al, , 2009. Previous studies have shown that S. pombe 2-Cys peroxiredoxin Tpx1 and its human ortholog Prx1 can directly interact with hemin (Normant et al, 2021;Watanabe et al, 2017). Therefore, we F I G U R E 3 Analysis of Srx1-GFP protein steady-state levels and its localization as a function of iron availability.…”
Section: Purified Srx1 Binds Heminmentioning
confidence: 99%
See 3 more Smart Citations